Correction: The performance of a lateral flow SARS-CoV-2 antibody assay and semi-autonomous SARS-CoV-2 antisense and sense RNA fluorescence in situ hybridization assay in a prospective cohort pilot study within a Dutch military population. - Inge D Wijnberg; Anton J Soons; Johan G Reimerink; Marit Wiersma; Marie Christine J Plat; Tom van Gool; Gijsbert J Jansen; Cornelis Stijnis; Jack G Koning; Adam Meijer (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0309091.].